Variable amplification of immunoglobulin lambda light-chain genes in human populations - Taub, R A; Hollis, G F; Hieter, P A; Korsmeyer, S; Waldmann, T A; Leder, P (Nature (London), 1983)
The human lambda immunoglobulin locus displays a series of restriction fragment length polymorphisms that are readily detected in small populations of normal individuals. Similar polymorphisms appear in populations of wild mice, suggesting that the lambda locus is subject to rapid variation within a single species. Here we show that the polymorphisms seen in the human lambda locus seem to have arisen from unequal meiotic crossing over, altering the number of lambda from as few as six to as many as nine per haploid genome. This expansion and contraction in the number of human lambda genes is significant in that it may affect an individual's capacity to produce variation among lambda light chain genes.